2021
DOI: 10.3390/vaccines9070761
|View full text |Cite
|
Sign up to set email alerts
|

Combating Human Viral Diseases: Will Plant-Based Vaccines Be the Answer?

Abstract: Molecular pharming or the technology of application of plants and plant cell culture to manufacture high-value recombinant proteins has progressed a long way over the last three decades. Whether generated in transgenic plants by stable expression or in plant virus-based transient expression systems, biopharmaceuticals have been produced to combat several human viral diseases that have impacted the world in pandemic proportions. Plants have been variously employed in expressing a host of viral antigens as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 293 publications
(284 reference statements)
0
16
0
Order By: Relevance
“…While the proof of concept that an immune response induced by oral vaccines has all the required properties to neutralize viral infections is well documented, making this immunity efficient is still problematic. Public concerns regarding the use of genetically modified plants and environmental risk assessments should also be considered for the economical evaluation of these vaccines' production on a large scale [111].…”
Section: Discussionmentioning
confidence: 99%
“…While the proof of concept that an immune response induced by oral vaccines has all the required properties to neutralize viral infections is well documented, making this immunity efficient is still problematic. Public concerns regarding the use of genetically modified plants and environmental risk assessments should also be considered for the economical evaluation of these vaccines' production on a large scale [111].…”
Section: Discussionmentioning
confidence: 99%
“…Even though plants can be stably modified, most approaches focus on transient expression, frequently using Agrobacterium tumefaciens or to a lesser extent other viruses such as Tobacco mosaic virus (TMV), a process that is less time-consuming and renders higher and more consistent yields [ 213 ]. Lately, chloroplast transformation has emerged as an alternative since it allows proteins to fold and accumulate in the subcellular compartment, even though this strategy still faces drawbacks regarding low efficiency and impaired glycosylation [ 217 ].…”
Section: Alternative Factories For Recombinant Vaccine Productionmentioning
confidence: 99%
“…The plant-produced VLPs were successful in preclinical trials and were able to induce both humoral and cellular immune responses in phases I and II trial in humans, presenting a satisfactory safety profile and modest results in phase III trials [210][211][212]. In the last years, several plant-based vaccine strategies are being assessed in clinical trials, developed against hepatitis B, cholera, Ebola, influenza, and other infectious diseases [213]. More recently, the COVID-19 pandemics pushed plant-made vaccines to the spotlight, with 3 phase 3 trials taking place targeting SARS-CoV-2 and presenting encouraging results [214].…”
Section: Alternative Factories For Recombinant Vaccine Productionmentioning
confidence: 99%
“…The vaccine was claimed to be able to trigger significant immune responses with a single dose and was also stable at room temperature [94]. These plant-based vaccines showed high immunogenicity and were well-tolerated in phase I, II, and III clinical trials [95,96]. However, other reports have revealed that the plant-produced vaccine contained plant-specific N-glycan epitopes that could cause immunogenic or allergic reactions in humans [97,98].…”
Section: Potential Of Microalgae For the Production Of Recombinant S-...mentioning
confidence: 99%